Management of severe acute exacerbations of COPD: an updated narrative review - Crisafulli, Ernesto; Barbeta, Enric; Ielpo, Antonella; Torres, Antoni (Multidisciplinary respiratory medicine, 2018)
Background Patients with chronic obstructive pulmonary disease (COPD) may experience an acute worsening of respiratory symptoms that results in additional therapy; this event is defined as a COPD exacerbation (AECOPD). Hospitalization for AECOPD is accompanied by a rapid decline in health status with a high risk of mortality or other negative outcomes such as need for endotracheal intubation or intensive care unit (ICU) admission. Treatments for AECOPD aim to minimize the negative impact of the current exacerbation and to prevent subsequent events, such as relapse or readmission to hospital. Main body In this narrative review, we update the scientific evidence about the in-hospital pharmacological and non-pharmacological treatments used in the management of a severe AECOPD. We review inhaled bronchodilators, steroids, and antibiotics for the pharmacological approach, and oxygen, high flow nasal cannulae (HFNC) oxygen therapy, non-invasive mechanical ventilation (NIMV) and pulmonary rehabilitation (PR) as non-pharmacological treatments. We also review some studies of non-conventional drugs that have been proposed for severe AECOPD. Conclusion Several treatments exist for severe AECOPD patients requiring hospitalization. Some treatments such as steroids and NIMV (in patients admitted with a hypercapnic acute respiratory failure and respiratory acidosis) are supported by strong evidence of their efficacy. HFNC oxygen therapy needs further prospective studies. Although antibiotics are preferred in ICU patients, there is a lack of evidence regarding the preferred drugs and optimal duration of treatment for non-ICU patients. Early rehabilitation, if associated with standard treatment of patients, is recommended due to its feasibility and safety. There are currently few promising new drugs or new applications of existing drugs.